REPRESENTASI MUSLIM DALAM SERIAL MS. MARVEL (2022) - Adiyatma, Irfandhika; Rahardjo, Turnomo; Yusriana, Amida (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The world of Hollywood films often presents Muslim identity as a secondary group related to acts of terrorism. This is due to several events in the past such as the events of September 9 2001. Since then Muslims have received a lot of discrimination from American society and are seen as a cruel and violent identity. After 21 years have passed, a superhero series by Marvel has emerged, namely Ms. Marvel. This series is a bold breakthrough from the MCU (Marvel Cinematic Universe) because it promotes Muslim identity as the main character. The aim of this research is to find out how Muslims are represented in the Ms. Marvel. This research uses qualitative research methods with a constructivism paradigm. The theory used in this series is Identity Negotiation Theory proposed by Stella Ting-Tomey using John Fiske's semiotic analysis method. The results of this research show that Muslim identity is displayed positively but still only partially. Positive Muslims can be seen through the depiction of Muslims as an identity that is equal to other cultural identities. This equality can be seen through various aspects such as camera angles that use eye level angles, the appointment of Muslims as main characters, and the friendship between Kamala and Bruno. Apart from that, positive Muslims are also depicted through aspects of the characterization of Muslim characters that seem humorous, dialogue that is not related to terrorism, as well as other aspects such as worship gestures that reflect a religious nature. However, unfortunately this depiction is still partial because Kamala's character is depicted as not wearing a hijab. The hijab is a mandatory attribute for a Muslim woman, but in this series, Kamala is shown wearing the hijab in only a few scenes. Suggestions for further research are to examine how Muslim identity is linked to other American minority identities such as Jews, blacks, Asians and others, using other semiotic analysis methods such as Umberto Eco or Roland Barthes.